ANALISIS CONSTITUTIONAL ENGINEERING PADA PUTUSAN MK NOMOR 135/PUU-XXII/2024 TERHADAP REDESAIN PEMILU SERENTAK TAHUN 2029 - Amin Nugrah Santoso; Kanza Indah Safitri (CV. Era Digital Nusantara, 2026)
Constitutional Court Decision Number 135/PUU-XXII/2024 represents a significant form of constitutional engineering within Indonesia’s constitutional system, particularly concerning the design of simultaneous elections. The ruling emerged as a response to the complexities experienced during the 2019 and 2024 simultaneous elections, which were considered to have imposed excessive administrative burdens, weakened the quality of democracy, and reduced voters’ ability to make rational political choices. This study examines how the concept of constitutional engineering is constructed in Constitutional Court Decision Number 135/PUU-XXII/2024 and analyzes its implications for the redesign of Indonesia’s simultaneous elections in 2029. The objective of this research is to identify the constitutional restructuring initiated by the Constitutional Court and to evaluate the new electoral framework established following the decision. This research employs a normative legal method using statutory, conceptual, and case approaches. Legal materials were obtained from Constitutional Court decisions, statutory regulations, and scholarly literature related to constitutional law and the theory of constitutional engineering. The data were analyzed qualitatively by examining the ratio decidendi of the decision and its constitutional implications for the national electoral system. The findings reveal that Constitutional Court Decision Number 135/PUU-XXII/2024 constitutes an effort of constitutional engineering through the reorganization of the simultaneous election model aimed at strengthening the presidential system, improving political representation, and simplifying electoral administration. The redesign of the 2029 elections is directed toward separating national and local electoral schemes, whereby the elections for President, the House of Representatives (DPR), and the Regional Representative Council (DPD) are conducted simultaneously at the national level, while regional head elections and Regional House of Representatives (DPRD) elections are held separately at a different time. This redesigned model is expected to reduce technical complexities in election management, reinforce political party institutionalization, enhance voter rationality, and promote greater governmental stability within Indonesia’s constitutional democracy. Therefore, the decision functions not merely as a judicial ruling, but also as an instrument of constitutional engineering that shapes a new direction for Indonesia’s electoral system toward a more proportional, efficient, and democratic simultaneous election model in 2029.